Evaluation of Cases of Non-Compressive Myelopathies- A Clinical Study - Praveen K; Shiby T G (Asian Journal of Medical Research, 2020)
Background: Myelopathy describes pathologic conditions that cause spinal cord, meningeal or perimeningeal space damage or dysfunction. The present study was conducted to assess cases of myelopathy. Subjects and Methods: The present study was conducted on 82 cases of myelopathy of both genders. Lumbar puncture was performed in all patients. Cerebrospinal fluid (CSF) was examined for protein, cells, and sugar. Results: Out of 82 patients, males were 52 and females were 30. There were 41 males and 14 females with idiopathic transverse myelitis and 11 males and 16 females with other acute myelopathies. Mean CSF protein in group I was 56.2 and in group II was 82.4, CSF cells were 28.5 in group I and 214.6 in group II, CSF sugar was 71.4 in group I and 62.7 in group II, RBS was 120.1 in group I and 116.3 in group II. The difference was significant (P< 0.05). Centromedullary involvement was seen in 95% in group I and 82% in group II, LETM was present in 82% in group I and77% in group II, contrast enhancement was seen in 31% in group I and 45% in group II, cord swelling was seen in 64% in group I and 52% in group II. The difference was significant (P< 0.05). Conclusion: Authors found that cases were of idiopathic transverse myelitis and acute myelopathies. MRI is useful in diagnosis of lesions.